The clinical relevance of neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio in chronic obstructive pulmonary disease with lung cancer - Ma, Aiping; Wang, Guangdong; Du, Yan; Guo, Weixi; Guo, Jiaxi; Hu, Yi; Bai, Dongyu; Huang, Huiping; Zhuang, Lianjin; Chen, Jinhan; Liu, Qun (Frontiers in Oncology, 2022)
Background: Chronic obstructive pulmonary disease (COPD) coexisting lung cancer is associated with severe mortality and worse prognosis. Inflammation plays an important role in common pathogenic pathways and disease progression. However, little studies have identified the clinical value of the neutrophil-to-lymphocyte ratio (NLR) or platelet-to-lymphocyte ratio (PLR) in COPD with lung cancer, which are systemic inflammatory response markers in blood. The study was aimed to determine the association of the NLR or PLR with clinical characteristics and whether NLR or PLR can be diagnostic markers for COPD with lung cancer. Methods: We conducted a retrospective analysis of 236 COPD patients with lung cancer and 500 patients without lung cancer (control group) between 2015 and 2021 in our study. Clinical information, blood routine examination and spirometry results were collected and analyzed. Receiver operating characteristic (ROC) curve was used to identify the best cutoff point of NLR or PLR. Multivariate logistic regression analysis was performed to evaluate the association of NLR or PLR with the diagnosis and prognosis of COPD with lung cancer. Results: Compared to patients in the only COPD group, the patients in the lung cancer group had a higher percentage of current smoking and emphysema. And it was found that NLR or PLR was significantly higher in the lung cancer group. Multivariate analysis has showed that age, smoking status, FEV1% pred, emphysema, NLR and PLR were independent risk factors for lung cancer development in the COPD. Further, the high level of NLR or PLR was associated with over 70 years old, current smoking status and ineligible-surgery treatment. The level of PLR or NLR markedly increased with hyper-coagulation status, the severity of airflow limitation and advanced progression of lung cancer. Additionally, the ROC analysis also revealed that elevated NLR or PLR was an independent predictor of COPD in lung cancer patients, TNM stage ⅢB-Ⅳ at first diagnosis in lung cancer and ineligible surgery in lung cancer patients. Conclusion: Increased NLR or PLR values might be an important and easily measurable inflammation biomarker to predict the diagnosis and severity of lung cancer with COPD.